Differential effects of four intramuscular sedatives on cardiorespiratory stability in juvenile guinea pigs (Cavia porcellus). - Ryan P Sixtus (Public Library of Science (PLoS), 2021)
Background Non-invasive physiological monitoring can induce stress in laboratory animals. Sedation reduces the level of restraint required, thereby improving the validity of physiological signals measured. However, sedatives may alter physiological equilibrium introducing unintended bias and/or, masking the experimental outcomes of interest. We aimed to investigate the cardiorespiratory effects of four short-acting sedatives in juvenile guinea pigs. Method 12 healthy, 38 (26-46) day-old Dunkin Hartley guinea pigs were included in this blinded, randomised, crossover design study. Animals were sedated by intramuscular injection using pre-established minimum effective doses of either alfaxalone (5 mg/kg), diazepam (5 mg/kg), ketamine (30 mg/kg), or midazolam (2 mg/kg) administered in random order with a minimum washout period of 48 hours between agents. Sedative depth, a composite score comprised of five assessment criteria, was observed every 5-min from dosing until arousal. Physiological monitoring of cardiorespiratory status included measures of heart rate, blood pressure, respiratory rate, and peripheral microvascular perfusion. Results Ketamine and alfaxalone were most effective in inducing stable sedation suitable for physiological monitoring, and diazepam less-so. Midazolam was unsuitable due to excessive hypersensitivity. All sedatives significantly increased heart rate above non-sedated control rates (P<0.0001), without altering blood pressure or microvascular perfusion. Alfaxalone and ketamine reduced respiratory rate relative to their control condition (P<0.0001, P = 0.05, respectively), but within normative ranges. Conclusion Ketamine and alfaxalone are the most effective sedatives for inducing short duration, stable sedation with minimal cardiorespiratory depression in guinea pigs, while diazepam is less-so. However, alfaxalone is the most appropriate sedative for longitudinal studies requiring multiple physiological timepoints.